A participação social na estruturação da política cultural em Oliveira (MG): uma análise à luz da sociologia pragmática - Ferreira, Thaís Caroline (2017)
The promulgation of the Federal Constitution, culminating with the reestablishment of the Brazilian Democracy, presented basic principles to the structure of the Brazilian cultural policy, being that, from this mark, structured into a decentralized and participative way, in a collaborative process between federated entities and civil society. On this perspective, they ruled and institutionalized, with the collaboration of the civil society, the National Plan of Culture and the National System of Culture, whose proposal is implementing them in the states and cities. However, the institutionalization and the implementation of state and city systems is still a process in progress, which requires the mobilization and efforts of the people involved with the cultural matter in the effectiveness of this process. Thus, we can assume that the involvement of the civil society, from the so-called social participation, is able to contribute to the organization of this policy. In this sense, we aimed, with the present work, understand how the social participation occurs in the organization of the cultural policy in Oliveira (MG), using the technological resources of the Pragmatic Sociology to analyze the engaging and the justification of the people involved in this process. At the very first moment, we examined the organization of the cultural policy of the city, next, we identified the mechanisms used to the social participation in this policy and its dynamics of working, and at last, we analyzed the logic of justification and engaging presented in the participative processes of the cultural policy of Oliveira, under the lights of the Pragmatic Sociology. We chose, in the methodology, by the qualitative approach, performing the survey kind exploitation and descriptive. The gathering of data occurred through documental analysis, non-participant observation and semi structured interviews. The data were analyzed through the resources of the Pragmatic Sociology, occurring the co-relation of the data with the regimes of engaging and with the common-worlds. As a result, it was possible to check the existence of different regimes and worlds at the participative spaces, being that the social participation occurs through mechanisms as the Municipal Conferences of Culture and the Municipal Cultural Policy Council, involving people who interact with the cultural field in the county of Oliveira (MG), collaborating to the implementing of the cultural policy, complying the demands of the ones who will use it.